Patulin Ameliorates Hypertrophied Lipid Accumulation and Lipopolysaccharide-Induced Inflammatory Response by Modulating Mitochondrial Respiration - Seulmin Hong; Seon Kyeong Park; Jangho Lee; Soo Hyun Park; Young-Soo Kim; Jae-Ho Park; Seungmin Yu; Yu Geon Lee (MDPI AG, 2023)
Patulin (PAT) is a natural mycotoxin found in decaying pome fruits. Although some toxicological studies have been conducted on PAT, recent research has highlighted its anticancer and antifungal effects. However, studies have yet to examine the effects and molecular mechanisms of PAT in other metabolic diseases. Obesity is a chronic disease caused by excessive food intake and abnormal lifestyle, leading to low-grade inflammation. Therefore, this study aimed to elucidate the effect of PAT on obesity at the cellular level. PAT treatment reduced lipid accumulation, suppressed glucose and LDL uptake, inhibited lipid deposition and triglyceride synthesis, upregulated fatty acid oxidation-related genes (Pgc1α), and downregulated adipogenic/lipogenic genes (Pparγ and C/ebpα) in hypertrophied 3T3-L1 adipocytes. Additionally, PAT treatment enhanced mitochondrial respiration and mass in differentiated adipocytes and alleviated inflammatory response in activated RAW 264.7 macrophages. Moreover, PAT treatment downregulated pro-inflammatory genes (il-6, Tnf-α, Cox-2, and inos), suppressed lipopolysaccharide (LPS)-induced increase in inflammatory mediators (IL-6, TNF-α, and NO), and restored mitochondrial oxidative function in LPS-stimulated macrophages by improving oxygen consumption and mitochondrial integrity and suppressing ROS generation. Overall, these findings suggest a potential for PAT in the prevention of lipid accumulation and inflammation-related disorders.